Sustainable Development Indicators - Goal 4: The Social Reality of Education in Yemen During the Period 2015-2024: A Sociological Analytical-Comparative Perspective - Hassan Baseed, Iman Abdulmalik (Social Empowerment Journal, 2025)
Yemeni society has been living in a war since 2015, which has led to a difference in the general social context of society. The education sector has been attempting to coexist regarding the war, especially after the stoppage of paying salaries of the employees of the administrative apparatus in the country. The study gains its importance by analyzing the nature of the social reality of education in Yemen, and the factors leading to it. The findings will show the factors causing the abuse of education, and will reach the most prominent findings and recommendations that should help improve the educational process in Yemen. The study aims to identify the quality of education and its problems during the war in Yemen by studying the social reality of education, and the factors of those problems that led to the establishment of the social reality of education in Yemen during 2010-2024. The study uses the analytical and comparative historical methodology, and it concludes that there is a defect in the educational process, which has contributed to the increase in the dropout rate from education, the change in school curricula does not meet the requirements of the labor market, and that the Ministry of Education does not benefit from university professors in developing school curricula in line with the labor market, as well as there are no punitive methods that deter the violators for not respecting teachers.